Modification optical properties of TiO2 nanostructure as solar cell. (November 2022) - Haider, Adawiya; Ali, Ghalib; Haider, Mohammed J.; Edan, Mahdi S.; Al-Obaidy, Rusal; Thamir, Amin; Hathal, Mustafa M.; Abbas, Ehsan M.; Al-Sheikh, Farooq
Abstract: In the process of this work, the Pulsed Laser Deposition (PLD) technique was used to deposit nanoparticles of pure titanium oxide (TiO2 ) onto a glass substrate at temperatures ranging from 100 to 400 degrees Celsius. This experiment made use of a Nd: YAG laser that had its frequency-doubled. The laser had a wavelength of 532 nanometers and an average laser strength of 800 millijoules. To explore the optical properties, transmittance spectrometry measurements were carried out for both visible and ultraviolet wavelengths. These measurements were carried out. The results of the optical transmittance test showed that it was more than 80 percent, which indicates that it is suitable for use in applications involving solar cells. The research was conducted on a number of optical constants, including the refractive index, the absorption coefficient, and the attenuation coefficient, and the values of these optical constants were determined. The value of the refractive index was found to be 2.49 when measured at a temperature of 400 degrees Celsius and a wavelength of 550 nanometers. Additionally, it was feasible to calculate the density of the titanium dioxide coating, which came out to be 3.6881 grams per cubic centimeter after the calculation was complete. The use of a numerical equation was utilized to ascertain the connection that exists between density and base temperature. It is an empirical equation that may be employed in the process of calculating the density of the components that are being used, and it has the potential to do so successfully. This equation is one of a kind since it was produced via the use of a theoretical computer program, and it is specific to the results that were obtained from the research.